Twardowski i Teresa - Szargot, Maciej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Monograph of Alicja Mazan-Mazurkiewicz „Liryka ks. Jana Twardowskiego. Spotkanie ze św. Teresą z Lisieux” is a reading of the works of a priest-poet through the prism of the person and the work of Saint Teresa of Lisieux, called “little Teresa”. It compares the works of a priest and Carmelite nun, as well as their personalities and biographies (above all – spiritual). The work is distinguished by research reliability, sensitivity and loyalty to texts. This is demonstrated by, for example, great interpretations of poems (e.g. „Niewidoma dziewczynka” and „Wierzę”), as well as themes (telephone, kiss, couple ...) and metaphors.
Twardowski and Teresa
Keywords: Jan Twardowski; Saint Teresa of Lisieux; lyrics; spirituality; comparative studies; św. Teresa z Lisieux; liryka; duchowość; komparatystyka